Pyoderma gangrenosum‐like oral ulcerations in an elderly patient. (December 2015) - Kaomongkolgit, Ruchadaporn; Subbalekha, Keskanya; Sawangarun, Wanlada; Thongprasom, Kobkan
Abstract : Objective: To present a case of pyoderma gangrenosum (PG)‐like oral ulcerations in an elderly patient. Background: PG is an uncommon idiopathic, ulcerative, chronic inflammatory cutaneous disorder of unknown etiology, which is associated with systemic diseases found in more than 50% of patients. Oral lesions of PG are extremely rare and have not been previously reported on chronic leukemia patient. Clinical report: This report presents the first case of a 73 year‐old man who had PG‐like oral ulcerations which offered the possibility of an initial finding of chronic myeloid leukemia. Conclusion: Clinicians should always take into consideration that PG in the oral mucosa is a recalcitrant ulcer and can precede the development of underlying clonal malignancy.